Inactivation of two oyster pathogens by photocatalysis and monitoring of changes in the microbiota of seawater: a case study on Ostreid Herpes Virus 1 µVar and Vibrio harveyi - Blanchon, Cécile; Toulza, Eve; Calvayrac, Christophe; Eichendorff, Stanislawa; Travers, Marie-Agnes; Vidal-Dupiol, Jeremie; Montagnani, C.; Escoubas, Jean-Michel; Stavrakakis, Christophe; Plantard, Gaël (HAL CCSD, 2024)
International audience The pollution of seawater by both biotic (bacteria, viruses) and abiotic contaminants (biocides, pharmaceutical residues) frequently leads to economic losses in aquaculture activities mostly mortality events caused by microbial infection. Advanced Oxidation Processes (AOPs) such as heterogeneous photocatalysis allow the removal of all organic contaminants present in water and therefore could reduce production losses in land-based farms. Oysters in land-based farms such as hatcheries and nurseries suffer from a large number of mortality events, resulting in significant losses. If photocatalysis has been widely studied for the decontamination, its application for disinfection is still overlooked, especially on seawater for viruses. We therefore studied seawater disinfection using the photocatalyis (UV365/TiO2) method in the context of Pacific oyster mortality syndrome (POMS). POMS has been defined as a polymicrobial disease involving an initial viral infection with Ostreid Herpes Virus 1, accompanied by multiple bacterial infections. We investigated the impact of treatment on Vibrio harveyi, a unique opportunistic pathogenic bacterium, and on a complex microbial community reflecting a natural POMS event. Viral inactivation was monitored using experimental infections to determine whether viral particles were still infectious after. Changes in the total bacterial community in seawater were studied by comparing UV365/TiO2 treatment with UV365-irradiated seawater and untreated seawater. In the case of OsHV-1, a 2-hour photocatalytic treatment prevents POMS disease and oyster mortality. The same treatment also inactivates 80% of viable Vibrio harveyi culture (c.a. 1.5 log). Since OsHV-1 and Vibrio harveyi are effectively inactivated without long-term destabilization of the total bacterial microbiota in the seawater, photocatalysis appears to be a relevant alternative for disinfecting seawater in land-based oyster beds.